2021
DOI: 10.3390/molecules26216689
|View full text |Cite
|
Sign up to set email alerts
|

Pt-Free Metal Nanocatalysts for the Oxygen Reduction Reaction Combining Experiment and Theory: An Overview

Abstract: The design and manufacture of highly efficient nanocatalysts for the oxygen reduction reaction (ORR) is key to achieve the massive use of proton exchange membrane fuel cells. Up to date, Pt nanocatalysts are widely used for the ORR, but they have various disadvantages such as high cost, limited activity and partial stability. Therefore, different strategies have been implemented to eliminate or reduce the use of Pt in the nanocatalysts for the ORR. Among these, Pt-free metal nanocatalysts have received conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 90 publications
(133 reference statements)
0
11
0
Order By: Relevance
“…A very interesting route for designing novel materials is combining theory and experiment [ 129 , 130 ]. It has been demonstrated that combining experimental results and DFT calculations is very efficient for designing novel toxic-gas sensors [ 131 , 132 , 133 ].…”
Section: Combined Theoretical and Experimental Studiesmentioning
confidence: 99%
“…A very interesting route for designing novel materials is combining theory and experiment [ 129 , 130 ]. It has been demonstrated that combining experimental results and DFT calculations is very efficient for designing novel toxic-gas sensors [ 131 , 132 , 133 ].…”
Section: Combined Theoretical and Experimental Studiesmentioning
confidence: 99%
“…Due to their unique properties, these clusters can be utilized for various technological applications in the fields of catalysis, electronics, and medicine, among others [11][12][13][14]. Specifically, in the field of catalysis, the interest in bimetallic systems formed by Pd alloyed with 3d transition metals has steadily grown, largely due to their promising catalytic efficiency [15][16][17][18][19][20]. For instance, PdNi/C nanoparticles have been evaluated for the ethanol oxidation reaction, where the Pd 2 Ni 3 /C catalyst exhibits higher activity and stability in alkaline media than the Pd/C catalyst [15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of high-performance fuel cells has received widespread attention. [1][2][3] However, oxygen reduction reaction (ORR), as an cathode half reaction in fuel cells, limits the efficiency in fuel cells, owing to its slow reaction kinetics process. The traditional Pt catalyst is the most effective catalyst to promote the ORR, but its practical application is limited by poor stability, high cost, and scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel cells with clean and sustainable features have been considered as a promising candidate to overcome the energy crisis caused by the continuous consumption of non‐renewable fossil fuels. Therefore, the development of high‐performance fuel cells has received widespread attention [1–3] . However, oxygen reduction reaction (ORR), as an cathode half reaction in fuel cells, limits the efficiency in fuel cells, owing to its slow reaction kinetics process.…”
Section: Introductionmentioning
confidence: 99%